Two conceptions of justice in Les Misérables - Bustillos García, Brenda Betzait (2023)
Les Misérables (Les Misérables) is a classic work of world literature written by the French writer Victor Hugo. In the novel we find different conceptions of justice and injustice; therefore, the reader must analyse different approaches to determine and compare the ethical choices of each of the characters. The story takes place in the 19th century, in a time of chaos, struggle, unrest, oppression and inequality. The backdrop is the French Revolution, an event that brought about great transformations. The narrative of Les Misérables is part of Romanticism, exposing issues related to certain values such as goodness and evil, justice and injustice, among others, represented by the characters, especially by the protagonist and the antagonist: Jean Valjean and Javert, respectively. Les Misérables neatly shows the nostalgia of a world full of contradictions, as part of the substratum of an entire era and artistic style. Through different intertwining stories, Victor Hugo develops the conflict between aesthetic and ethical experience.